Common long-term complications of adult congenital heart disease: avoid falling in a H.E.A.P. (2nd April 2016) - Ministeri, M; Alonso-Gonzalez, R; Swan, L; Dimopoulos, K
ABSTRACT: Advances in cardiology and cardiac surgery have transformed the outlook for patients with congenital heart disease (CHD) so that currently 85% of neonates with CHD survive into adult life. Although early surgery has transformed the outcome of these patients, it has not been curative. Heart failure, endocarditis, arrhythmias and pulmonary hypertension are the most common long term complications of adults with CHD. Adults with CHD benefit from tertiary expert care and early recognition of long-term complications and timely management are essential. However, it is as important that primary care physicians and general adult cardiologists are able to recognise the signs and symptoms of such complications, raise the alarm, referring patients early to specialist adult congenital heart disease (ACHD) care, and provide initial care. In this paper, we provide an overview of the most commonly encountered long-term complications in ACHD and describe current state of the art management as provided in tertiary specialist centres.